2022
DOI: 10.21601/ijese/12089
|View full text |Cite
|
Sign up to set email alerts
|

A Gender-based Investigation of Indian Senior Secondary Students’ Misconceptions about Plant Reproduction through Concept Inventory

Abstract: The central objective of this study was to unveil the misconceptions and their sources through the responses of Indian senior secondary (n=102; 54 boys and 48 girls) students about plant reproduction. A concept inventory with correct and incorrect statements was designed to elicit the misconceptions among class XII students. A semi-structured interview of selected students followed this exercise to report the sources of misconceptions from students' perspectives. Descriptive statistics like mean and percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In the context of natural science, including the topic of reproduction in living things especially plant, students may encounter various misconceptions due to the complexity of the concepts and the potential for misunderstandings plant reproduction which is one of the concepts in biology which requires a level of conceptual understanding and very close to everyday life. This material has interrelated subconcepts that allows students to understand the necessary initial understanding of the material if students' initial understanding is not strong then to understand the next sub-concept prone to misconceptions (Roy & Mohapatra, 2022). Misconceptions about pollination and seed dispersal mechanisms in plants were detected in the majority of grade 5 to 12 students (Vosniadou, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of natural science, including the topic of reproduction in living things especially plant, students may encounter various misconceptions due to the complexity of the concepts and the potential for misunderstandings plant reproduction which is one of the concepts in biology which requires a level of conceptual understanding and very close to everyday life. This material has interrelated subconcepts that allows students to understand the necessary initial understanding of the material if students' initial understanding is not strong then to understand the next sub-concept prone to misconceptions (Roy & Mohapatra, 2022). Misconceptions about pollination and seed dispersal mechanisms in plants were detected in the majority of grade 5 to 12 students (Vosniadou, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Misconceptions as scientifically inaccurate interpretations with erroneous ideas and views [7]. Misconceptions come from various sources; students, teachers, textbooks, and the environment [8]. In formal education, scientific misconceptions have been found through interactions between teachers and students who may experience misconceptions in the learning process [9].…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that students have difficulty in understanding the topics such as fruit formation, germination and seed dispersal. In addition, with many studies has been revealed misconceptions about plants (Bell, 1985;Brown & Schwartz, 2009;Parker et al, 2012;Roy & Mohapatra, 2022;Södervik et al, 2015;Svandova, 2014;Wang, 2007;Yangin et al, 2014;Yürük et al, 2011). In the study conducted by Jewell (2002), it was revealed that students were unable to realise that all flowering plants bear fruit, and that they associated germination with the emergence of leaves rather than shoots and roots.…”
Section: Introductionmentioning
confidence: 99%